Sorghum kombucha’s impact on lean pigs and obese pigs during early weight loss - Gaya Macaneiro, Maria Eugenia (My University, 2025)
The use of pigs in research has expanded to serving as valuable translational models for humans. This thesis investigates the body composition changes and behavioral effects of fermented sorghum kombucha in lean Ossabaw pigs and obese Ossabaw pigs during early weight loss. Ossabaw pigs are an established model for studying obesity due to their genetic predisposition to store fat under high-calorie diets. For the first 16 weeks after enrollment, pigs were first grown into a lean body type using a standard diet or an obese body type using a hypocaloric, high-fat, high-fructose corn syrup diet (i.e., Western Diet). Then, liquid supplementation was applied while obese pigs underwent a 6-week weight management program (lean pigs had no dietary changes). The liquid supplementation was twice daily administration (1 L per day) of either an isocaloric control solution or fermented sorghum kombucha. In Study 1, besides the body weight, weekly ultrasound imaging was used to assess body composition, including back fat thickness and loin eye area. Results revealed that fermented sorghum kombucha was associated with reduced average daily gain and increased back fat loss in obese pigs compared to those receiving the isocaloric control. These outcomes suggest that sorghum kombucha may influence adipose tissue metabolism during the early stages of weight loss. Study 2 explored how the supplement affected feeding motivation, social interaction, and cognitive flexibility using an automated cognitive feeder test. Behavioral observations revealed that obese pigs, during the early weight loss period, receiving sorghum kombucha demonstrated changes in latency to drink, frequency of bowl switching, and decreased dominance indices, suggesting that sorghum kombucha may modulate social interactions and feeding behaviors. Together, these findings show that fermented sorghum kombucha may influence early physiological and behavioral markers of obesity in pigs, offering insights into nutritional strategies for metabolic health.
Keywords: Sorghum kombucha; Ossabaw pigs; Obesity; Dominance; Cognition; Swine